2022
DOI: 10.1186/s12876-022-02382-y
|View full text |Cite
|
Sign up to set email alerts
|

The gut microbiota composition in patients with right- and left-sided colorectal cancer and after curative colectomy, as analyzed by 16S rRNA gene amplicon sequencing

Abstract: Background Gut pathological microbial imbalance or dysbiosis is closely associated with colorectal cancer. Although there are observable differences in molecular and clinical characteristics between patients with right- and left-sided colon cancer, differences in their gut microbiomes have not been thoroughly investigated. Furthermore, subsequent changes in microbiota status after partial colectomy remain unknown. We examined the human gut microbiota composition to determine its relationship wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 42 publications
2
5
1
Order By: Relevance
“…Our study revealed heterogeneity in the bacteriome of CRC patients, specially related to the diversity and taxonomic composition. Although factors such as the location and stage of CRC are known to potentially influence the variability of the microbiomes ( Sheng et al, 2019 ; Suga et al, 2022 ), we did not observe associations in our study population, which may be due to the limited number of patients. Regarding the stage of CRC, the genus Pediococcus was significantly reduced in advanced cases ( Figure 8D ), and showed a negative co-occurrence with Desulfovibrio , suggesting a potential protective role against CRC progression ( Figure 6 ).…”
Section: Discussioncontrasting
confidence: 69%
“…Our study revealed heterogeneity in the bacteriome of CRC patients, specially related to the diversity and taxonomic composition. Although factors such as the location and stage of CRC are known to potentially influence the variability of the microbiomes ( Sheng et al, 2019 ; Suga et al, 2022 ), we did not observe associations in our study population, which may be due to the limited number of patients. Regarding the stage of CRC, the genus Pediococcus was significantly reduced in advanced cases ( Figure 8D ), and showed a negative co-occurrence with Desulfovibrio , suggesting a potential protective role against CRC progression ( Figure 6 ).…”
Section: Discussioncontrasting
confidence: 69%
“…[1,[26][27][28]); and (b) our ANHAC group showed dysbiosis, overall. Consistent with (b), the random forest could not differentiate the ANHAC group from a grouping of cancer diagnoses (see Supplementary Information and compare [1,[29][30][31][32]). However, the absence of healthy controls limits characterization of our ANHAC group and the nature of its dysbiosis.…”
Section: Discussionsupporting
confidence: 66%
“…We found that beta-diversity was significantly different, with distinct microbial profiles emerging after surgical resection of right-sided CRC compared to left-sided CRC. A previous study reported lower levels of Gemellaceae in patients who underwent right CRC resection, while the Firmicutes phylum was found to be abundant in those who underwent sigmoid colon cancer resection ( Suga et al, 2022 ). Taken together, our results underscore the difference in microbiome composition based on the location of resection.…”
Section: Discussionmentioning
confidence: 97%